KETERAMPILAN MENULIS TEKS DESKRIPSI DI KURIKULUM MERDEKA KELAS VIIA SMP NEGERI 5 SUNGAI RAYA - Samsinah, Linda; Wartiningsih, Agus; Sanulita, Henny (Universitas Tanjungpura, 2025)
This research examines the general problem of discussing and analyzing descriptive texts written by student sin Indonesian language lessons in the Merdeka Curriculum ofanalyzing descriptive texts from the aspects of title, structure and linguistic rules from the work sheets that have been created by students. The research method used was a descriptive method in the form of qualitative research. The source of research data is class VII A students. The data in this research are the results of students' assignments in writing descriptive texts. The data collection techniq ueusedin this researchis document study.Basedon the research results, looking at the title aspect, it was found that 10 people received very good assessment criteria, 10 people received good assessment criteria. Judging from the aspect of the identification structure, 6 people received very good assessment criteria, 11 people received good assessment criteria, 2 people received adequate assessment criteria,1 person received poor assessment criteria. Judging from the structural aspect of the section description, 2 people got a score of 5 with good assessment criteria. 10 people received adequate assessment criteria, 8 people received inadequate assessment criteria. In the conclusion impression structure, 2 people got good assessment criteria, 10 people got adequate assessment criteria. There were 5 students who got a score of 2 with poor assessment criteria. In the aspect of linguistic rules, 2 people received very good assessment criteria, 6 people received good assessment criteria, 7 people received adequate assessment.There were 3 people who received poor assessment criteria.